The Effect of Digital Comic on the Students’ Mastery in English Simple Present Tense - S, Alif Iskandar.; Jismulatif, Jismulatif; Supriusman, Supriusman (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research was conducted in order to discover the effect of digital comic on the students’ mastery in English simple present tense in writing context. This research used quantitative research with pre-experimental design. One-group Pretest-Posttest Design was selected. In this design, one group of students was selected in order to measure their level of progress before and after the treatment. There were 23 students who participate in the pre-test in day 1. After that, they participated in the treatment process by reading the digital comic from day 2 to day 7. In day 8, the students participate in the posttest to determine their progress after reading the digital comic. The researcher also applied a normality test to ensure the data was normally distributed and then continued by conducted the paired sample T-test. The mean value from the pretest was only 55.52. However, in the posttest, the mean value reached 62.56. From this change, it can be concluded that the digital comic that was used in this research can improve the students’ mastery in English simple present.